DOPPELGÄNGERS AND DOUBLES IN LITERATURE: EXPLORING IDENTITY, PSYCHOLOGICAL CONFLICT, AND THE FRAGMENTED SELF - Madaminova Umida Rustam qizi (International Journal of Literature and Language Studies, 2026)
The doppelgänger, or double, motif has been a significant part of literary traditions through the ages and across cultures. The idea has its roots in folklore and mythology, but the concept evolved into a powerful literary tool, allowing authors to explore questions of identity, internal struggle, morality and the fractured self. This article analyses selected works of Gothic, Romantic and modern literary traditions to explore the role and importance of doppelgängers and doubles in literature. The study, through a qualitative textual analysis, examines the ways in which doubles represent hidden desires, repressed emotions and internal conflicts. The findings suggest that the literary doubles destabilize fixed identities and offer a way for writers to explore the complexities of the human mind. The article concludes that the doppelgänger remains a relevant and versatile literary motif because it reflects enduring concerns about selfhood, alienation, and psychological fragmentation.